Prevalence of REM sleep behavior disorder in Sun City, Arizona. Issue 1 (January 2020) - Shprecher, David R.; Serrano, Geidy E.; Zhang, Nan; Intorcia, Anthony; Davis, Kathryn J.; Glass, Michael; Curry, Jasmine; Walker, Jessica; Cutler, Brett; Callan, Michael; Garcia, Angelica; Sue, Lucia I.; et al.
Abstract: Objective: To determine prevalence of REM sleep behavior disorder (RBD) [prodromal Lewy body disease] in Sun City, Arizona. Patients and methods: We attempted, by telephone and mail, a survey using the RBD single item question for probable RBD (pRBD) and the Innsbruck RBD Inventory. Individuals answering "yes" to 4/5 Inventory questions were considered to have high likelihood RBD (HL-RBD.) Results: Response rate was 484/3000 individuals contacted (16%), mean age 78; 48 (9.9%) endorsed pRBD by RBD1Q; 16 (3.3%) had HL-pRBD. Prevalence of idiopathic cases (without neurodegenerative disease) was 8.8% pRBD and 2.8% HL-RBD. Conclusion: Our estimated definite RBD prevalence of 1.7% (61.3% of HL-RBD) was similar to previous community-based studies. Abstract : Clinical research; Nervous system; Neurology; Neuroscience; Pathology; Parkinson disease; Dementia with lewy bodies; REM sleep behavior disorder; Lewy body dementia